Feasibility of microalgae cultivation system using membrane-separated CO2 derived from biogas in wastewater treatment plants. (November 2017) - Takabe, Yugo; Himeno, Shuji; Okayasu, Yuji; Minamiyama, Mizuhiko; Komatsu, Toshiya; Nanjo, Kouhei; Yamasaki, Yukiyo; Uematsu, Ryuji
Abstract: Utilising CO2 from biogas as a carbon source can introduce energy production systems incorporating microalgae cultivation into wastewater treatment plants (WWTPs). In this study, the effects of utilising membrane-separated CO2 (MSC; CO2 content: 983 ± 11 dm 3  m −3 )—obtained from biogas using a newly developed separation system—on indigenous microalgae cultivation with treated effluents was investigated. Assuming model cultivation systems, energy balance analysis was conducted to evaluate the feasibility of MSC utilisation and its superiority over flue gas CO2 (FC) from power plants (PPs). Scenarios 1 and 2 used generated biogas of 11.6 and 116 dm 3  s −1, and produced MSC (carbon based) were 0.802 and 8.02 g s −1, respectively. Experiments comparing MSC (suspended solids (SS): 166 ± 23 mg dm −3 ; higher heating value (HHV): 21.1 ± 0.46 kJ g −1 ) with commercial CO2 (SS: 176 ± 16 mg dm −3 ; HHV: 21.2 ± 0.90 kJ g −1 ) revealed no negative effects on microalgae activity, biomass production, or energy content. Energy revenue of the MSC utilisation system was 27.0 MJ per 1 kg injected MSC, which is greater than the energy costs (18.2 and 17.1 MJ kg −1 in scenarios 1 and 2, respectively). MSC utilisation is energetically feasible, and energetically superior to FC utilisation when the PP-to-WWTP distance is over 0.6 and 1.9 km in scenarios 1 and 2, respectively. Highlights: Membrane separated CO2 (MSC) from biogas was used for indigenous microalgae growth. Feasibility of MSC utilisation was evaluated in model microalgae cultivation system. There were no negative effects of MSC on biomass and energy production. MSC utilisation in wastewater treatment plants (WWTPs) is energetically feasible. MSC is energetically superior to flue gas CO2 up to distance from power plant to WWTP.